Studies on the Effect of Seed Material on Germination and Initial Vigour of Simarouba glauca Under Shade Net Conditions - Prasanthi, L.; Maheshwara Reddy, P.; Sudhakar, P. S.; Balakrishna Babu, B. (Indian Forester, 2010)
No abstract